Basic Photophysical Properties of meso-Bis(pyren-2-yl)porphyrin: An Isomer of Pyrene-Substituted Porphyrins - Tomita, Shohei; Hirabayashi, Kazunori; Shimizu, Toshio; Goto, Kenta; Sugiura, Ken-ichi (Synthesis, 2017)
The Suzuki–Miyaura coupling reaction of pyren-2-yl boronic acid ester with a meso-dibromodiphenylporphyrin derivative was carried out to give another pyrene-substituted porphyrin. The electrophilic substitution reaction occurred selectively on the porphyrin nucleus of this molecule. The introduced pyrenes acted as a light-harvesting antenna.
Keywords: porphyrin; pyrene; Suzuki–Miyaura coupling; light-harvesting